PPARδ Attenuates Alcohol-Mediated Insulin Resistance by Enhancing Fatty Acid-Induced Mitochondrial Uncoupling and Antioxidant Defense in Skeletal Muscle - Koh, Jin-Ho; Kim, Ki-Hoon; Park, Sol-Yi; Kim, Yong-Woon; Kim, Jong-Yeon (Frontiers in Physiology, 2020)
Alcohol consumption leads to the dysfunctions of multiple organs including liver, heart, and skeletal muscle. Alcohol effects on insulin resistance in liver are well evidenced, whereas its effects in skeletal muscle remain controversial. Emerging evidence indicates that alcohol promotes adipose tissue dysfunction, which may induce organ dysregulation. We show that ethanol (EtOH) consumption reduces the activations of AMPK and mTOR and the expressions of CPT1 and GLUT4 in myotube. We observed chronic EtOH consumption increases free fatty acid levels in plasma and triglyceride (TG) accumulation in skeletal muscle, and that these increases induce insulin resistance and decrease glucose uptake. Hence, ethanol dysregulates metabolic factors and induces TG accumulation. We found peroxisome proliferator-activated receptor β/δ (PPARδ) activation recovers AMPK activation and increases fatty acid transporter (Carnitine-acylcarnitine translocase, CACT) expression. These effects may contribute to enhance mitochondrial activation when a fatty acid substrate via UCP3, thus reduces EtOH-induced increases in TG levels in skeletal muscle. In addition, PPARδ activation recovered EtOH-induced loss of AKT phosphorylation at serine 473 via rictor activation. Importantly, PPARδ activation enhanced mitochondrial uncoupling via UCP3. Taken together, the study shows PPARδ enhances fatty acid oxidation and uncoupled respiration via UCP3 and protects against EtOH-induced lipotoxicity and insulin resistance in skeletal muscle.